First report of Pantoea ananatis causing leaf blight disease of rice in Peninsular Malaysia - Azizi, M. M. F.; Zulperi, D.; Rahman, M. A. A.; Abdul Basir, B.; Othman, N. A.; Ismail, S. I.; Hata, E. M.; Ina Salwany, M. Y.; Abdullah, M. A. F. (American Phytopathological Society, 2019)
The genus Pantoea contains pathogenic bacteria causing destructive diseases on rice (Oryzae sativa L.) because they reduce the quality, hence affecting the yield of rice production. Rice infected by Pantoea species can exhibit severe diseases such as leaf blight, stem necrosis, grain discoloration, and damaged germplasm of rice seeds (Mondal et al. 2011). In September 2017 and April 2018, bacterial leaf blight disease of rice (MR269 and CL varieties) was observed in rice fields located in the states of Selangor and Kedah, Malaysia, with 80% disease incidence. Disease symptoms observed were water-soaked stripes with yellowing color, which later turned into brown stripes on the upper part of leaves (Kini et al. 2017). The causal agent was isolated from symptomatic leaf pieces after surface sterilization using 75% ethanol for 30 s and rinsing thrice in sterilized water containing 1% NaClO. Samples were macerated in sterilized water, streaked on semiselective King’s B agar medium, and incubated for 48 h at 28°C. Ten representative isolates (PA1, PA3, PA5, PA6, PA7, PA8, PA9, PA10, PA11, and PA12) were isolated from the diseased samples. Bacterial colonies were yellow pigmented, raised, irregular border, and translucent with smooth margin, resembling the characteristics of Pantoea ananatis (Mondal et al. 2011). All isolates were subjected to biochemical tests, revealing gram-negative facultative anaerobe, motile, positive for catalase and gelatin tests, hydrolyzing starch, not producing hydrosulfuric acid, indole positive, and capable of producing acetoin. The DNA of all isolates was extracted using a Geneaid DNA Isolation Kit (Geneaid Biotech, Taiwan). Polymerase chain reaction (PCR) amplification based on the gyrb gene fragment developed from 26 genomes of Pantoea species was performed on all isolates, each producing a ∼600-bp amplicon (Kini et al. 2017). The amplicons were sequenced, and the sequences were submitted to GenBank database (accession nos. MH698458, MH698460, MH698462, MH698463, MH698464, MH698465, MH698466, MH698467, MH698468, and MH698469). A BLASTn search revealed 100% nucleotide identity of all isolates to P. ananatis ARC60 reference strain (accession no. KX385187). The phylogenetic tree constructed from all isolates based on the gyrb gene sequences indicated 99% similarity to P. ananatis reference strains (accession nos. KX385187, KX342014, and KF554589). PCR amplification with P. ananatis-specific gene, PANA_1080, which encodes for a hypothetical protein of the pathogen, produced a ∼900-bp amplicon each (Asselin et al. 2016), and a BLASTn search showed 96% identity to the P. ananatis LMG 20103 reference strain (accession no. CP001875). The nucleotide sequences of all isolates were later deposited to GenBank database (accession nos. MK348547 to MK348556). To test pathogenicity, 10 ml of 108 CFU/ml bacterial suspension of each isolate was inoculated into 35-day-old rice seedlings of MR269 and CL varieties by using a leaf-clipping method, and they were kept in the greenhouse with temperature ranging from 26 to 35°C, performed in triplicate (Ke et al. 2017). Control rice seedlings were inoculated with sterilized water. All isolates of P. ananatis produced symptoms within 2 weeks postinoculation. Symptoms appeared similar to those of natural infections, including yellowish necrotic water-soaked lesion. Control rice seedlings remained asymptomatic. Bacteria were reisolated from symptomatic leaves and further identified as P. ananatis by PANA_1080 gene sequencing, fulfilling the Koch’s postulates. To the best of our knowledge, this is the first report of P. ananatis causing leaf blight disease of rice in Malaysia. With the aid of molecular-based approaches, a better understanding on the taxonomy of P. ananatis will help to improve and develop effective disease control strategies against this wide-spreading bacterial pathogen of rice in Malaysia.